A review of complex hormone regulation in thyroid cancer: novel insights beyond the hypothalamus–pituitary–thyroid axis - Chen, Liu-han; Xie, Tao; Lei, Qian; Gu, Yan-rui; Sun, Chuan-zheng (Frontiers in Endocrinology, 2024)
Like the ovaries and prostate, the thyroid exhibits characteristic hormone secretion and regulation. Thyroid cancer (TC), especially differentiated thyroid carcinoma, has typical sex-specific and age-specific hormone-driven clinical features. Previous research has primarily focused on the effects of thyroid stimulating hormone, thyroid hormones, and estrogens on the onset and progression of TC, while the roles of growth hormone (GH), androgens, and glucocorticoids have largely been overlooked. Similarly, few studies have investigated the interactions between hormones and hormone systems. In fact, numerous studies of patients with acromegaly have shown that serum levels of GH and insulin-like growth factor-1 (IGF-1) may be associated with the onset and progression of TC, although the influences of age, sex, and other risk factors, such as obesity and stress, remain unclear.Sex hormones, the GH/IGF axis, and glucocorticoids are likely involved in the onset and progression of TC by regulating the tumor microenvironment and metabolism. The aim of this review was to clarify the roles of hormones and hormone systems in TC, especially papillary thyroid carcinoma, as references for further investigations.